A new lead-acid battery state-of-health evaluation method using electrochemical impedance spectroscopy for second life in rural electrification systems. (1st August 2022) - Mohsin, Muhammad; Picot, Antoine; Maussion, Pascal
Abstract: Providing electricity at an affordable price wherever one lives is still a concern. The use of batteries to store electrical energy is very common practice but can be a weak link in a system due to failures. Re-using old lead-acid car batteries discarded from thermal engine vehicles could be a cheap electricity storage solution for remote areas, in line with the principles of frugal innovation. Evaluating the State of Health (SoH) of these batteries is of the utmost importance for the second life of car lead-acid batteries. Some methods exist, such as the two-pulse method or the internal resistance method, but their results are not always reliable. Electrochemical Impedance Spectroscopy is another classical technique; however, a reliable formula is still required to link the SoH and EIS with unknown battery history. A new and original way to determine the SoH from EIS is detailed in this work. Old and new batteries are used for experimental prediction at different states of charge. A small average prediction error is found for 56 different configurations. The newly proposed method is named "CdS based method". Results from this method, are compared to results from existing methods and improvement is clear. Highlights: State-of-health (SoH) of lead-acid battery is studied when no history data is available. Second-life batteries are focused on for this research. Electrochemical impedance spectroscopy is used for the analysis. Corrosion and sulphation are given a 20% and 80% share respectively for ageing of lead-acid battery. A new SoH method is provided named "CdS based method".